2014
DOI: 10.1038/ncomms4428
|View full text |Cite
|
Sign up to set email alerts
|

The serine protease prostasin regulates hepatic insulin sensitivity by modulating TLR4 signalling

Abstract: The effects of high-fat diet (HFD) and postprandial endotoxemia on the development of type 2 diabetes are not fully understood. Here we show that the serine protease prostasin (PRSS8) regulates hepatic insulin sensitivity by modulating Toll-like receptor 4 (TLR4)-mediated signalling. HFD triggers the suppression of PRSS8 expression by inducing endoplasmic reticulum (ER) stress and increases the TLR4 level in the liver. PRSS8 releases the ectodomain of TLR4 by cleaving it, which results in a reduction in the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 39 publications
4
63
1
Order By: Relevance
“…Consistent with our findings, Uchimura et al recently reported that hepatic Tlr4 plays an important role in regulating glucose metabolism and insulin sensitivity in mice 27 .…”
Section: Resultssupporting
confidence: 93%
“…Consistent with our findings, Uchimura et al recently reported that hepatic Tlr4 plays an important role in regulating glucose metabolism and insulin sensitivity in mice 27 .…”
Section: Resultssupporting
confidence: 93%
“…The reported sizes of TLR4 fragments were different, suggesting that different enzymes may be involved in this process. So far, neutrophil elastase and prostasin (a serine protease) have been identified to cleave the extracellular region of TLR4 [25, 26]. The present study clearly demonstrates that 1,25D 3 causes ectodomain shedding of TLR4.…”
Section: Discussionsupporting
confidence: 57%
“…As noted above, ADAM10-mediated ectodomain shedding of TLR4 resulted in a significant decrease in the response of cells to LPS in terms of p38 phosphorylation and ICAM-1 expression. In HepG2 cells [26], the ectodomain cleavage of TLR4 mediated by the serine protease prostasin was also shown to decrease the receptor activity. In contrast, the ectodomain cleavage of TLR4 mediated by neutrophil elastase in macrophage was accompanied by an increased production of inflammatory cytokines [25].…”
Section: Discussionmentioning
confidence: 99%
“…This surprising finding is not in accordance with several other studies, suggesting that mice lacking MyD88 in the brain or in the gut are protected against both diet-induced obesity and insulin resistance. [11][12][13][14] Therefore, our data strongly suggest that MyD88 differentially contributes to the regulation of energy and glucose homeostasis depending on the targeted organ. This also partially explains the quantity of conflicting data existing when investigating whole-body Myd88 deletion and its impact of obesity and related disorders.…”
Section: Discussionmentioning
confidence: 60%